Correlation of Myocardial Strain and Late Gadolinium Enhancement by Cardiac Magnetic Resonance After a First Anterior ST-Segment Elevation Myocardial Infarction - Yu, Shiqin; Zhou, Jinying; Yang, Kai; Chen, Xiuyu; Zheng, Yucong; Zhao, Kankan; Song, Jialin; Ji, Keshan; Zhou, Peng; Yan, Hongbing; Zhao, Shihua (Frontiers in Cardiovascular Medicine, 2021)
Objectives: To investigate the correlation of cardiac magnetic resonance (CMR) feature-tracking with conventional CMR parameters in patients with a first anterior ST-segment elevation myocardial infarction (STEMI). Methods: This sub-analysis of OCTAMI (Optical Coherence Tomography Examination in Acute Myocardial Infarction) registry included 129 patients who finished a CMR examination 1 month after a first anterior STEMI. Cine images were applied to calculate both global and segmental left ventricular peak strain parameters. The patients were divided into two groups by left ventricular ejection fraction (LVEF) and compared with 42 healthy controls. Segmental late gadolinium enhancement (LGE) was graded according to LGE transmurality as follows: (1) >0 to ≤ 25%; (2) >25 to ≤ 50%; (3) >50 to ≤ 75%; (4) >75%. Left ventricle was divided into infarcted, adjacent, and remote regions to assess regional function. Results: Compared with controls, global radial (28.39 ± 5.08% vs. 38.54 ± 9.27%, p < 0.05), circumferential (−16.91 ± 2.11% vs. −20.77 ± 2.78%, p < 0.05), and longitudinal (−13.06 ± 2.15 vs. −15.52 ± 2.69, p < 0.05) strains were impaired in STEMI patients with normal LVEF (≥55%). Strain parameters were strongly associated with LGE (radial: r = 0.65; circumferential: r = 0.69; longitudinal: r = 0.61; all p < 0.05). A significant and stepwise impairment of global strains was observed in groups divided by LGE tertiles. Furthermore, segmental strain was different in various degrees of LGE transmurality especially for radial and circumferential strain. Strains of adjacent region were better than infarcted region in radial and circumferential directions and worse than remote region in all three directions. Conclusion: Global and regional strain could stratify different extent and transmurality of LGE, respectively. Although without LGE, adjacent region had impaired strains comparing with remote region.